Biossurfactantes: propriedades anticorrosivas, antibiofilmes e antimicrobianas - Lívia Vieira de Araujo (Química Nova, 2013)
Due to the importance of biofilms in the food industry, new products are being developed to enhance the efficiency of cleaning food-contact surfaces. Biosurfactants could be an alternative to synthetic products. The major advantages of biosurfactants over synthetic detergents are their low toxicity and highly biodegradable nature. Biosurfactants may also exhibit antimicrobial, anti-adhesive and anticorrosive activity concomitantly. In this review, we emphasize the potential application of biosurfactants as surface coating agents to prevent corrosion and decrease planktonic and sessile microbial growth.